Handling Fever In Toddlers At Homes In The Village Of Manarap Lama - Darini Kurniawati; Eirene E.M Gaghauna; Malisa Ariani (Jurnal Empathy Pengabdian Kepada Masyarakat, 2021)
Background: The prevalence of fever at the age of 0-4 years was 33.4%, cough was 28.7% and diarrhea was 11.4%. Central Agency Statistics in Indonesia (2012), children with fever as many as 90,245 children, in 2013 as many as 112,511 children. From field observations and interviews with some communities, the main problem was that the community had not been able to calculate drug doses for children under five and did not understand how to handle fever in children under five. The purpose is increase the level of knowledge and skill about fever handling of parents who have children under five in Manarap Village. Methods: Pre-test and Post-test, Educational counseling, training to measure temperature with a thermometer, training to calculate the dose of fever medicine for children under five, training in handling fever in children under five. The number of respondents are 14 people, total implementation of activities is 1 month, but educational activities and interviews are carried out for 1 day but at different times, then a follow-up plan is made after the activity. Results: Increased knowledge can be seen from the post-test value which is higher than the pre-test value, participants can measure body temperature with a thermometer correctly, participants can calculate the dose of paracetamol fever medicine for children under five, participants understand the handling of fever in children under five. Conclusion: Community service activities to treat fever in children under five through education have increased the knowledge and understanding of participants from the results of the pretest and post-test with a significant increase in scores. The hands-on practice of using a thermometer, compressing and calculating the right dose helped participants understand.